Analysis of carotenogenic gene expression in petals and leaves of carnation (Dianthus caryophyllus L.). Issue 4 (25th June 2013) - Ohmiya, Akemi; Tanase, Koji; Hirashima, Masumi; Yamamizo, Chihiro; Yagi, Masafumi
Abstract: Carnation ( Dianthus caryophyllus L.) belongs to the family Caryophyllaceae in the order Caryophyllales. Plants in this order do not accumulate carotenoids in petals. To understand how carotenoid accumulation is controlled in carnation petals, we analysed the expression of genes related to carotenoid accumulation. Petals at an early stage of development accumulated small amounts of carotenoids. As petals matured, their carotenoid content decreased to extremely low levels. In contrast, carnation leaves contained substantial amounts of carotenoids that are essential for photosynthesis. Most of the carotenogenic genes were expressed in petals at levels similar to those in leaves, and the expression levels of these genes increased during petal development. Genes encoding phytoene synthase and lycopene ε‐cyclase were exceptions. Their expression levels in petals were very low compared with those in leaves. Expression of the gene encoding carotenoid cleavage dioxygenase 4 was detected in neither leaves nor petals. These data suggest that the low levels of carotenoids in carnation petals are caused not by enzymatic degradation but rather by low rates of carotenoid biosynthesis.